Integrated Heterostructure of PDA/Bi‐AgIn5S8/TiO2 for Photoelectrochemical Hydrogen Production: Understanding the Synergistic Effect of Multilayer Structure. Issue 10 (28th February 2018) - Guan, Peng; Bai, Hongye; Li, Chunfa; Ge, Yilin; Xu, Dongbo; Chen, Biyi; Xia, Teng; Fan, Weiqiang; Shi, Weidong
Abstract: Overcoming one of most challenging limitations of bare TiO2 with large bandgap can be achieved by rational design and fabrication of heterostructures. Multicomponent sulfides with a nature of tunable band structure can be a good alternative to decorating TiO2, but there remains a major trade‐off between the high efficiency and the long‐term durability, so the stability issue must be addressed upon the use of sulfides. Here, an effective strategy is demonstrated with Bi‐doped AgIn5 S8 (Bi‐AgIn5 S8 ) decorated TiO2 photoanode, where twofold enhancement of the photocurrent is achieved. More importantly, it is the first time to integrate polydopamine passivation layer and AgIn5 S8 for simultaneously enhancing the solar conversion efficiency and stability. The incident photon‐to‐current conversion efficiency value is tuned up to 45% (0.4 V vs Ag/AgCl), and the photocurrent density can keep for 90.8% after 5 h. Corresponding hydrogen evolution rate has increased to 8.6 µmol h −1, which is three times higher than that of bare TiO2 . Abstract : Integration of polydopamine (PDA)/Bi‐AgIn5 S8 /TiO2 can simultaneously enhance the solar conversion efficiency and stability. The hydrogen evolution rate of optimal sample is enhanced to 8.6 µmol h −1, which is three times higher than that of bare TiO2 .